2022
DOI: 10.1126/sciimmunol.ade9888
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to BA.4/5 S protein drives neutralization of Omicron BA.1, BA.2, BA.2.12.1, and BA.4/5 in vaccine-experienced humans and mice

Abstract: The SARS-CoV-2 Omicron variant and its sublineages show pronounced viral escape from neutralizing antibodies elicited by vaccination or prior SARS-CoV-2 variant infection owing to over 30 amino acid alterations within the spike (S) glycoprotein. Breakthrough infection of vaccinated individuals with Omicron sublineages BA.1 and BA.2 is associated with distinct patterns of cross-neutralizing activity against SARS-CoV-2 variants of concern (VOCs). In continuation of our previous work, we characterized the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 31 publications
2
28
0
Order By: Relevance
“…Similarly, previous mRNA vaccine studies in mice on an ancestral primed background demonstrated a broadening of immune responses upon boosting with ancestral/BA.1 bivalent vaccines compared with monovalent preparations [32,33].…”
Section: Our Monovalent and Bivalent Cv0501 Vaccines Induced Comparab...mentioning
confidence: 60%
See 1 more Smart Citation
“…Similarly, previous mRNA vaccine studies in mice on an ancestral primed background demonstrated a broadening of immune responses upon boosting with ancestral/BA.1 bivalent vaccines compared with monovalent preparations [32,33].…”
Section: Our Monovalent and Bivalent Cv0501 Vaccines Induced Comparab...mentioning
confidence: 60%
“…The objective of this study was to assess the immunogenicity and efficacy of vaccine candidate, CV0501, which encodes the S protein of the Omicron variant BA. [32,33].…”
Section: Cv0501 Protects Against Weight Loss and Viral Replication In...mentioning
confidence: 99%
“…Overall, our data point towards a potential benefit of bivalent vaccination for inducing a broad immune response. Similarly, previous mRNA vaccine studies in mice on an ancestral primed background demonstrated a broadening of immune responses upon boosting with ancestral/BA.1 bivalent vaccines compared with monovalent preparations [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 76%
“…Omi BA.1). Both bivalent mRNA and BBIBP-CorV/ZSVG-02-O prime-boost show improved response against VOCs absent in the vaccines ( Scheaffer et al, 2023 ; Muik et al, 2022 ). To understand the reason underlying the broadened cross-activity by the ZSVG-02-O boost, we analyzed the composition of total IgG in the sera from animals received the single dose ZSVG-02-O following the BBIBP-CorV prime.…”
Section: Discussionmentioning
confidence: 98%
“…Those studies show a single Omicron-specific boost also induce similar antibody titers across the multiple strains. Compared with Omicron-specific mRNA vaccines from Moderna (mRNA-1273.529) ( Scheaffer et al, 2023 ) and BioNtech (Omi BA.1) ( Muik et al, 2022 ), ZSVG-02-O produced almost identical Nab responses in naïve animals against WT, Delta and BA.1 VOCs. However, a heterologous BBIBP-CorV/ZSVG-02-O prime-boost strategy produced a broadened immune response more similar to the bivalent mRNA-1273.214 from Moderna ( Scheaffer et al, 2023 ) and BioNtech (BNT162b2 +.…”
Section: Discussionmentioning
confidence: 99%